The use of Usability Tests in Website-Based Student Report Value Processing Information Systems - Arip Solehudin; Nono Heryana; Rieke Retnosary (Buana Information Technology and Computer Sciences (BIT and CS), 2021)
Abstract - The information system for processing studentreport cards based on the website is a system that providesinformation on student activity reports online in the form of grade reports and related student information based on theweb, thus helping speed and quality in delivering information.Problems that occur in processing report cards at SMPN 2 Telagasari are currently still using report cards and inputtingstudent scores is still manual. This study aims to build a valueinformation system that makes it easier to check, record, and report computerized student grade data. In addition, by being web-based, data information can be accessed at any time. This website uses XAMPP as a web server for system design and MySQL as a database. The design of the login menu consisting of admins, teachers, and students has separate access when opening the application so that the security of the program is maintained. Testing this website using black-box testing and Likert scale usability testing to make it easier forauthors to assess whether this online report card processing information system website can facilitate users.